An integrated informatics curriculum in a baccalaureate nursing program. - Travis, L. L. (American Medical Informatics Association, 1991)
As health care requirements change, nurses will not only have to process and communicate more information, but the nature and types of this information will dramatically change as well. It is imperative that nurses understand the potential information technologies offer to assist the nurse in this expanded role. This paper describes an innovative endeavor to incorporate information technology with its undergraduate nursing program. The challenge was to design a program that would help develop the students' skills to critically appraise their information needs and conceptually evaluate the utility of gathering information in providing patient care. After completing the first nursing informatics course, there was an increase in the students' perception and understanding of the uses of information technology to support the nursing process in providing patient care.